2018
DOI: 10.1051/matecconf/201819604037
|View full text |Cite
|
Sign up to set email alerts
|

Transient method measured thermal properties of concrete with microspheres and latex based addition

Abstract: The goal of the performed research was to determine the influence of microspheres from fly ash and the latex based addition on the thermal properties of concrete. The tested additions were used in two different proportions each and they were combined with each other. As a reference two series of concrete were used: one without any addition and another with 0.2% of air entraining agent. The thermal properties were measured using transient method with ISOMET 2114 apparatus. No clear trends were observed in case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It was found that microspheres added to concrete reduce the compressive strength of all the modified concrete series presented in [3]. Jaskulski and Kubissa also showed that microspheres that are used as an additive to concretes have the potential to reduce thermal conductivity [4]. In the case of samples fully saturated with water, the obtained values of thermal conductivity, in almost all cases, did not differ from the values obtained for the reference samples.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…It was found that microspheres added to concrete reduce the compressive strength of all the modified concrete series presented in [3]. Jaskulski and Kubissa also showed that microspheres that are used as an additive to concretes have the potential to reduce thermal conductivity [4]. In the case of samples fully saturated with water, the obtained values of thermal conductivity, in almost all cases, did not differ from the values obtained for the reference samples.…”
Section: Introductionmentioning
confidence: 82%
“…There are many studies that have aimed to improve the thermal and strength properties of modified concretes [1][2][3][4]. Serina et al investigated the effect of the addition of aerogel on the strength and thermal properties of concrete composites.…”
Section: Introductionmentioning
confidence: 99%